A Prototype of Lecturer Course Allocation System - Sheikh, Mohamed Ahmed (2012)
This project is an implementation of a lecturer course allocation system (LECAS) which enables every lecturer can register courses by online as well as can view course schedule. The goal of is prototype is to provide the course schedules that would allow lectures to register courses that they plan to teach for the coming semester in the fast and possible ways. The objective of LECAS is to provide lecturers to get a convenient and efficient way during registering the courses. There are four users that can access the system such as; admin, lecturers, coordinator, and head department, each of them have different privileges in which they can access through internet and a web browser anytime and anywhere. Furthermore, this prototype has been developed by using java Servlet page (JSP) with MySQL for database. This prototype was developed based on the proposed requirement of system and was evaluated by using perceived usefulness and ease of use where the respondents are from University Utara Malaysia (UUM) lecturers. The feedbacks from 30 respondents about the system prototype are quite good which are showed with 5.46 grand mean for perceived usefulness factor and 5.37 grand mean for perceived ease of use factor with the scale of 7. Therefore, it can be concluded that the prototype is useful and easy to use. This prototype is expected to facilitate the other university to develop and enhance the system for lecturer registration time.